The Effect of The Application of Good Corporate Governance (GCG) Principles on Job Satisfaction and Employee Performance - Rio Mubaraq Nazam; Rojuaniah Rojuaniah (Jurnal Indonesia Sosial Teknologi, 2024)
Applying the principles of good corporate governance in general is very important in all companies, especially in the banking world. Good corporate governance principles make all stakeholders feel fairness, transparency, independence, accountability, and accountability. This study aims to analyse the effect of applying good corporate governance principles on job satisfaction and employee performance, as well as the effect of job satisfaction on employee performance. Public trust in state-owned banks is higher than in private banks. The researcher chose BNI as the research object because BNI is the only state-owned bank that operates full branches globally and is very good at implementing good corporate governance, as evidenced by obtaining a very trusted predicate based on the Corporate Governance Perception Index (CGPI) score. Specifically, the object of research is permanent employees of BNI Regional Office 15 located in East Jatinegara, Jakarta. This study used a survey by distributing questionnaires to 125 respondents. The research method uses SEM PLS. The results showed that applying good corporate governance principles positively affected job satisfaction and employee performance, but job satisfaction did not influence employee performance. The contribution of this research is expected to provide managerial implications for redesigning positions, promotions, salaries, or rewards for permanent employees to provide job satisfaction to employees.